MAKNA KOMUNIKASI VERBAL DAN UNSUR NONVERBALNYA DALAM TUTURAN KONSTATIF DI KELAS I SEKOLAH DASAR - Taufina Taufina (Universitas Negeri Malang, 2015)
Abstract: Verbal communication and its nonverbal elements were the base of the formation of the mindset and the positive behaviors of the first graders of elementary schools. One of the forms of the verbal communication and its nonverbal elements needed observing was the constative utterances. The constative utterances were those which were produced to say and to describe facts which the truth could be sought and their values could be seen after the teaching and learning was done. Therefore, the teachers’ skills in precisely producing the constative utterances were absolutely needed. The precision in producing the constative utterances and their nonverbal elements could improve the confidence and the learning enthusiasm of the students. Teachers should be able to produce constative utterances and their nonverbal elements effectively during the teaching and learning processes so that the goals of the teaching and learning could be achieved and the atmosphere could be conducive. Abstrak: Komunikasi verbal dan unsur nonverbalnya menjadi dasar pembentuk pola pikir dan perilaku positif siswa kelas I sekolah dasar. Salah satu bentuk komunikasi verbal dan unsur nonverbal yang perlu diperhatikan adalah tuturan konstatif. Tuturan konstatif merupakan tuturan yang pengutaraannya digunakan untuk mengatakan sesuatu, menggambarkan fakta-fakta yang bisa dicari kebenarannya, dan nilainya dapat dilihat setelah dilakukan proses pembelajaran. Untuk itu, kepiawaian guru dalam mengungkapkan tuturan konstatif dan unsur nonverbalnya secara tepat mutlak diperlukan. Ketepatan pengungkapan tuturan konstatif dan unsur nonverbalnya dapat meningkatkan rasa percaya diri dan antusiasme siswa dalam belajar. Guru hendaknya dapat mengungkapkan tuturan konstatif dan unsur nonverbalnya secara efektif dalam proses pembelajaran sehingga tujuan pembelajaran tercapai dan suasananya menjadi kondusif.